Inhibitory Deficits, Delay Aversion and Preschool AD/HD: Implications for the Dual Pathway Model - Lindy Dalen; Edmund J. S. Sonuga-Barke; Martin Hall; Bob Remington (Neural Plasticity)
The dual pathway model proposes the existence of separate and neurobiologically distinct cognitive (inhibitory and more general executive dysfunction) and motivational (delay aversion) developmental routes to AD/HD. The study reported in this paper explores the relation between inhibitory deficits and delay aversion and their association with AD/HD in a group of three-year-old children. Children identified as having a pre-school equivalent of AD/HD (N=19) and controls (N=19), matched for gender and IQ, completed a battery of inhibition and delay tasks. Correlational and factor analysis supported a dissociation between inhibitory deficits (go-no-go, set shifting) and delay aversion (choice delay) with delay of gratification cross-loading. Children with AD/HD displayed more inhibitory deficits and were more delay averse than controls. The data support the value of the distinction between motivational and cognitive pathways to AD/HD. Furthermore, the data suggest that such a distinction is apparent relatively early on during development.